Patterns of hair pulling in trichotillomania: an ecological momentary assessment study - Gallinat, Christina; Moessner, Markus; Wilhelm, Maximilian; Keuthen, Nancy J.; Bauer, Stephanie (Journal of Obsessive-Compulsive and Related Disorders, 2024)
Trichotillomania (TTM) research lacks an ecologically valid phenomenological description despite increasing research efforts. Previous studies primarily rely on retrospective cross-sectional data, emphasizing the need for longitudinal high-frequency assessments to capture the variability of hair pulling. The objective of this study was to describe hair pulling patterns and episode characteristics by means of ecological momentary assessment (EMA), and to compare those parameters between focused and automatic episodes. Study procedures included an online screening, a diagnostic interview via telephone, a comprehensive self-report questionnaire and a 10-day EMA-protocol (7 EMAs/day). Data from 61 individuals who met diagnostic criteria for TTM (age: M = 29.3, SD = 7.47; 92% female) were analyzed (3948 EMAs; 1217 episodes). Participants reported a mean number of 2.00 (SD = 2.31; range: 0-4.9) episodes per day. One third did not report any days without episodes. Hair pulling showed a relatively even distribution throughout the day. Most prominent triggers were tension and visual/tactile cues. The latter were more relevant in focused episodes, whereas “habit/routine” scored higher in automatic episodes. The results suggest that hair pulling occurs not sporadic but is rather present in daily life. Using real-time data from a clinical sample, the study enhances our comprehension of the phenomenology of TTM which may ultimately advance TTM research.
Online verfügbar: 11. September 2024, Artikelversion: 14. September 2024
Gesehen am 20.11.2024